2020
DOI: 10.1071/hc19007
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ evaluations of the standard and modified pedometer-based Green Prescription

Abstract: INTRODUCTIONThe Green Prescription is a primary care programme designed to increase physical activity in individuals with low activity levels. Older adults tend to engage in insufficient physical activity to obtain health-related gain. AIMTo examine participants’ ratings of the Healthy Steps intervention and to assess how participants rated the use of a pedometer-based Green Prescription in aiding their physical activity. METHODSIn total, 330 community-dwelling older adults who have low levels of activity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…They should learn how judiciously utilize financial resources from the ESI funds and European Investment Bank. As stated before (24)(25)(26)(27), "social policy should encourage the development of formal services in rural areas and elaborate policy measures for informal caregivers," also in greenhouses, which can be a more effective and efficient organization of LTC, as already shown by Hlebec et al (28).…”
Section: Conclusion and Further Directions Of Activitiesmentioning
confidence: 86%
See 2 more Smart Citations
“…They should learn how judiciously utilize financial resources from the ESI funds and European Investment Bank. As stated before (24)(25)(26)(27), "social policy should encourage the development of formal services in rural areas and elaborate policy measures for informal caregivers," also in greenhouses, which can be a more effective and efficient organization of LTC, as already shown by Hlebec et al (28).…”
Section: Conclusion and Further Directions Of Activitiesmentioning
confidence: 86%
“…What are the useful methods that can help develop optimal decision-making procedures at given constraints?” These would be essential questions in the European silver economy. The European initiative of the silver economy ( 5 ) and the smart eco-social villages ( 18 , 24 , 25 , 26 , 27 ) supports the idea of faster development of ambient assisted living technologies. These results can be ingredients of an innovative platform of the SSVs, ensuring that the increased needs of the older adults for safety, comfort, and environmentally friendly living is met easily, even though the dynamics of ageing is high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walking is one of the most basic, simple and popular physical activities [29]. In this study, a step-counting App was downloaded on the smartphone of each participant.…”
Section: Pedometermentioning
confidence: 99%
“…Patel et al found that elderly patients like receiving Green Prescriptions and if they receive a pedometer to measure their activity they are more active than if they receive a standard Green Prescription alone. 6 Ellis and Aitken 7 report a carefully nuanced description of the sexual identities and practices of New Zealand youth aged 16-19 years and Ker et al 8 report the success of a clinic focused on meeting the needs of patients in a university health clinic who wish to explore gender affirming therapy. Key messages from this paper reinforce patients' positive experiences of the accessibility, timeliness, affordability and acceptability of the primary care they received.…”
mentioning
confidence: 99%